Design drawing - Ching, Francis D.K.; Juroszek, Steven P. (New Jersey : Wiley, Hoboken, 2019)
Readers will gain a greater appreciation of the techniques presented in the book through the power of animation, video, and 3D models. Market description (Please include secondary markets) Students of Architecture, Interior Design, Landscape Architecture, and the Fine Arts (appropriate for use in focused drawing courses, or in Design Studio courses where drawing is an important component), Design Professionals who are interested in honing their design drawing skills.
Drawing from observation. Line and shape -- Tone and texture -- Form and structure -- Space and depth -- Drawing systems. Pictorial systems -- Multiview drawings -- Paraline drawings -- Perspective drawings -- Drawing from the imagination. Speculative drawing -- Diagramming -- Drawing composition -- Presentation drawing.
Includes index.
Keywords: ARCHITECTURAL DRAWING